Endoplasmic Reticulum–Mitochondria Contact Sites and Neurodegeneration - Xu, Lingna; Wang, Xi; Tong, Chao (Frontiers in Cell and Developmental Biology, 2020)
Endoplasmic reticulum-mitochondria contact sites (ERMCSs) are dynamic contact regions with a 10-30 nm distance between endoplasmic reticulum (ER) and mitochondria. ERMCSs regulate a variety of biological processes, including lipid transfer, calcium homeostasis, autophagy, and mitochondrial dynamics, et al. The dysfunction of ERMCS is closely related to various neurodegenerative diseases, including Parkinson’s disease (PD), Alzheimer’s disease (AD), and amyotrophic lateral sclerosis (ALS). In this review, we will summarize the current knowledge of the components and the organization of ERMCSs, the methods for monitoring ERMCSs, and the physiological functions of ERMCSs in different model systems. Meantime, we will emphasis the current understanding of the malfunction of ERMCSs and their potential roles in neurodegenerative diseases.